Durability Evaluation of Cement Board produced from Untreated and Pre-treated Empty Fruit Bunch Fibre through Accelerating Ageing - P, Peter; N M Z, Nik Soh; Z A, Akasah; M A, Mannan (OP Publishing, 2020)
Durability issue known that natural fibre tends to degrades in cementitious matrix particularly when in hot and humid exposure for a period of time. This experimental approach evaluates the potential of EFB cement board's durability in accelerated ageing condition. Initially, the EFB fibres are pre-treated for 24 hours by being soaked in 1% NaOH solution and oven-dried at 103±2°C. Cement boards of 1300 kg/m3 density are fabricated in the laboratory, with 2.5:1:2 ratio of ordinary Portland cement, EFB fibre and water with 3% CaCl2. Accelerated ageing assessment of hot water immersion for 10 days, 30 days and 60 days also wet dry cycle for 5 cycle, 15 cycle and 30 cycle at 70°C temperature are then conducted. The tested samples reveal finding ranges in modulus of rupture (MOR) of 3.98 – 9.11 MPa; modulus of elasticity (MOE) of 1056 – 4699 MPa; internal bonding (IB) of 0.28 – 0.53 MPa and thickness swelling (TS) of 1.66 – 9.25%. In addition, the field emission scanning electron microscope (FESEM) showed degradation mechanism of EFB cement board of before and after the accelerated ageing assessment. Conclusively, the findings showed that, accelerated ageing approach for durability assessment of cement boards could be done in quantifying the durability of samples in shorter time.